Study on the Physiological Characteristics of Sunflower Treated With Bacterial Fertilizer - Tury, Rita; Tóth, Szilárd Zsolt; Kaprinyák, Tünde; Lehoczky, Éva; Bélteki, Ildikó; Láposi, Réka (Journal of Central European Green Innovation, 2025)
In 2019, in the experimental area on Kompolt, we tested the effect of Mikro-Vital in sunflower crops in a large-plot experiment using 2 doses (1 l ha-1 and 2 l ha-1). The bacterial fertilizers were applied to the chernozem brown forest soil at sowing. At the beginning of July, before flowering, the relative chlorophyll content of the leaves was measured in vivo with field instruments (portable spectroradiometer and SPAD) and spectral vegetation indices were determined, which, in addition to photosynthetic processes, allow us to infer the stress tolerance of the plants and the nitrogen and water content of the leaves. These parameters are the most important determinants of fertility. We also measured the average yield at harvest. In the year of the study, weather conditions were not ideal for sunflower development. The minimal rainfall in spring resulted in poor crop development after sowing. Chlorophyll vegetation indices also indicated a significant positive effect of the bacterial fertilizer treatment, and photochemical activity (PRI), leaf water content (PWI) were higher compared to the control plots. In the control treatment, stress sensitivity (SIPI) and the amount of protective pigments (CRI, ARI) were higher. Water shortages also occurred at flowering, resulting in a medium average yield for all plots, which was lower than the average of Heves County, Northern Hungary and the country. Based on our tests, a treatment of 1 l ha-1 is considered optimal.
Keywords: plant conditioner; sunflower; in vivo measurements; SPAD-value; vegetation indices